AR Supporting System for Pool Games Using a Camera-Mounted Handheld Display. (21st October 2008) - Uchiyama, Hideaki; Saito, Hideo
Abstract : This paper presents a pool supporting system with a camera-mounted handheld display based on augmented reality technology. By using our system, users can get supporting information when they once capture a pool table. They can also watch visual aids through the display while they are capturing the table. First, our system estimates ball positions on the table with one image taken from an arbitrary viewpoint. Next, our system provides several shooting ways considering the next shooting way. Finally, our system presents visual aids such as shooting direction and ball behavior. Main purpose of our system is to estimate and analyze the distribution of balls and to present visual aids. Our system is implemented without special equipment such as a magnetic sensor or artificial markers. For evaluating our system, the accuracy of ball positions and the effectiveness of our supporting information are presented